Assessing cancer patients’ quality of life and coping mechanisms in radiotherapy department of the University College Hospital Ibadan (2013)
Background: Cancer is often associated with a lot of pain and suffering. These suggest that coping with the symptoms, diagnosis and treatment of cancer is a major life stressor that is capable of influencing patients’ quality of life (QoL). Purpose: The purpose of the study is to assess the relationship between cancer patients’ QoL dimensions and coping strategies in the Radiotherapy Department of the University College Hospital Ibadan, Nigeria. Methods: Data were collected on clinic days from all available and consenting cancer patients who were receiving treatment at the radiotherapy department. Participants were informed of their right to decline to fill the questionnaires. Result: In this study, 237 cancer patients participated. They had an age range of 15 to 95 years with a mean age of 49.91 years. There was significant inverse relationship between physical well-being with behavioural disengagement, venting, planning and self-blame (p<0.05); social/family well-being has significant linear relationship with active coping, emotional support, positive reframing, instrumental support, acceptance and religion (p<0.05); emotional well-being has significant inverse relationship with behavioural disengagement and self-blame (p<0.05); functional well-being has significant linear relationship with active coping, instrumental support and acceptance (p<0.05). Conclusion: It is important to assess cancer patients for the kind of coping strategies they are adopting to use in coping with their cancer burden, thereby guiding against lower QoL due to negative coping strategies. Intervention programmes could be developed to help cancer patients adopt more positive and effective coping strategies to improve patients’ QoL.